Nanoparticle-enabled concurrent modulation of phagocytosis and repolarization of macrophages for enhanced cancer immunotherapy. (December 2022) - Zhang, Jing-Yang; Chen, Fang-Man; Liu, Rong; Luo, Jia-Qi; Huang, Yong-Cong; Shu, Na; Zheng, Sui-Juan; Shao, Dan; Leong, Kam W.; Du, Jin-Zhi
Abstract: Activating macrophages for cancer immunotherapy has attracted intensive attention in recent years, but faces two major challenges. First, tumor-associated macrophages (TAMs) are predominately pro-tumorigenic M2 phenotype. Second, the phagocytosis of macrophages to cancer cells is severely inhibited by the upregulation of 'don't eat me' signals. In this study, we identified that resiquimod (R848), a small-molecule toll-like receptor 7/8 agonist, could promote the phagocytosis of macrophages while reprogramming macrophages to the anti-tumoral M1 phenotype. This pro-phagocytic effect could be further improved via the combination with anti-SIRPα antibody (aSIRPα). We then constructed a disulfide-bridged mesoporous silica nanoparticle (MSN)-based delivery system (RMSN-aSIRPα) for the co-delivery of R848 and aSIRPα to potentiate macrophage-mediated cancer immunotherapy. RMSN-aSIRPα was prepared by loading R848 into the cavity, and adsorbing aSIRPα on the surface of MSNs. aSIRPα interacts with SIRPα on macrophages to block the CD47–SIRPα axis, and synergized with R848 to promote macrophage phagocytosis. Meanwhile, R848 stimulated M2-to-M1 repolarization of TAMs in the tumor microenvironment (TME). In animal studies with aggressive melanoma and breast cancer models, RMSN-aSIRPα significantly improved the antitumor efficacy and resulted in immunostimulatory TME by reducing the abundance of M2 macrophages and facilitating tumor infiltration of CD8 + T cells. These findings demonstrate that the nanoparticle-enabled combination of macrophage repolarization and CD47-SIRPα blockade can amplify macrophage-based immune response. Graphical Abstract: ga1 Highlights: Resiquimod (R848) was revealed to promote phagocytosis of macrophages. The combination of R848 with SIRPα antibody (aSIRPα) further increased such an ability. A redox-responsive mesoporous silica nanoparticle was constructed for the co-delivery of R848 and aSIRPα. Combination of SIRPα blockade and R848 synergistically promoted the macrophage-mediated immunotherapy.